1-[(4-Nitrophenyl)sulfonyl]-4-phenylpiperazine treatment after brain irradiation preserves cognitive function in mice. Issue 10 (15th April 2020) - Bhat, Kruttika; Medina, Paul; He, Ling; Zhang, Le; Saki, Mohammad; Ioannidis, Angeliki; Nguyen, Nhan T; Sodhi, Sirajbir S; Sung, David; Magyar, Clara E; Liau, Linda M; Kornblum, Harley I; et al.
Abstract: Background: Normal tissue toxicity is an inevitable consequence of primary or secondary brain tumor radiotherapy. Cranial irradiation commonly leads to neurocognitive deficits that manifest months or years after treatment. Mechanistically, radiation-induced loss of neural stem/progenitor cells, neuroinflammation, and demyelination are contributing factors that lead to progressive cognitive decline. Methods: The effects of 1-[(4-nitrophenyl)sulfonyl]-4-phenylpiperazine (NSPP) on irradiated murine neurospheres, microglia cells, and patient-derived gliomaspheres were assessed by sphere-formation assays, flow cytometry, and interleukin (IL)-6 enzyme-linked immunosorbent assay. Activation of the hedgehog pathway was studied by quantitative reverse transcription PCR. The in vivo effects of NSPP were analyzed using flow cytometry, sphere-formation assays, immunohistochemistry, behavioral testing, and an intracranial mouse model of glioblastoma. Results: We report that NSPP mitigates radiation-induced normal tissue toxicity in the brains of mice. NSPP treatment significantly increased the number of neural stem/progenitor cells after brain irradiation in female animals, and inhibited radiation-induced microglia activation and expression of the pro-inflammatory cytokine IL-6. Behavioral testing revealed that treatment with NSPP after radiotherapy was able to successfully mitigate radiation-induced decline in memory function of the brain. In mouse models of glioblastoma, NSPP showed no toxicity and did not interfere with the growth-delaying effects of radiation. Conclusions: We conclude that NSPP has the potential to mitigate cognitive decline in patients undergoing partial or whole brain irradiation without promoting tumor growth and that the use of this compound as a radiation mitigator of radiation late effects on the central nervous system warrants further investigation.